Influence of Dynamics of Actors and Information on the Organic Supply Chain - Md. Hasan Maksud Chowdhury; Md. Mamun Habib; Samsinar Md. Sidin (ExcelingTech, 2023)
The agricultural sector throughout the world has seen shifting significantly by suitably using e-technology. A good number of studies have been conducted on agriculture and food security. The growth rate of world organic farming or business increases to more than the growth rate of traditional agriculture. In Bangladesh the pace of growth of organic agriculture is insignificant. The organic agriculture or organic supply chain in Bangladesh was scarcely studied. Hence, an intensive study is needed for the organic agriculture industry to pursue the organic supply chain that leads to a promising growth of organic business. A great deal of research has been conducted to explore the factors that may influence the organic supply chain and growth of the organic business. Several theories such as the diffusion of innovation theory, theory of planned behavior, marketing system and price of organic products, and quality function deployment have been studied and proposed to enhance the understanding of the issue. The integration of all these literature and theories has attracted the researcher’s attention. Thus, this study aims to explore the influence of information systems, e-technology, and the dynamics of the actors (consumer, retailer, intermediaries, transporter, farmer, and basic suppliers) on the organic supply chain enhancing the growth of the organic business. By adopting secondary data with collected data (primary data) using self-administrated questionnaires the research work was evaluated. A total of 389 responses from the organic agriculture industrial actors, consumers, and transporters were collected using stratified random sampling methods. To inspect and analyze data, Path Analysis and Structural Equation Modeling (SEM) techniques were used with AMOS. The results of the study indicated that the proposed model provided a good understanding of the factors influencing the organic supply chain. From the result, it was also revealed that the organic supply chain has a significant impact on the growth of organic farming and organic consumers and the performance of organic businesses. The research objectives of this study were accomplished and all research hypotheses were supported. This study theoretically offers useful information and collected data might help to further research relevant to the organic supply chain. In addition, the study finds a way to foster a better understanding and knowledge of the organic supply chain. It is encouraged to do future research to study the factors and information and impact of the organic supply chain from various aspects.Keywords: organic supply chain, e-technology, organic agriculture, growth of organic business, SEM, AMOS